Semiotic Analysis of Roland Barthes' Theory in the Poem "Cinta yang Agung" by Kahlil Gibran - Nisa Aulia Antonia (Research in Education, Technology, and Multiculture, 2023)
Abstract: This study aims to examine semiotics using Roland Barthes' theory in one of Kahlil Gibran's poems entitled "Cinta yang Agung". The research method used is a qualitative approach using semiotic analysis as an analytical tool. The poem "Love the Great" was chosen as the object of research because it contains deep and complex meanings, and involves the use of signs in forming hidden meanings and messages. The research that will be discussed, namely regarding the five Roland Barthes codes and analyzing each sign contained in the data. It is hoped that the results of this study can provide a deeper understanding of the meaning and messages contained in the poem "Cinta yang Agung" by Kahlil Gibran through Roland Barthes' semiotic analysis.    Keywords: semiotic studies, Roland Barthes theory, poetry.